Relação entre polimorfismos genéticos e níveis de citocinas com a doença do enxerto contra o hospedeiro aguda no transplante alogênico de células-tronco hematopoiéticas - Renata Goncalves de Resende (2010)
The graft versus host disease (GVHD) is a major cause of morbidity andmortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Genetic polymorphisms are associated with functional differences in the expression of cytokines and can lead to changes in the clinical course of disease. Although knowledge about the pathogenesis of the GVHD has been confirmed in recent years, few studies show the contribution of cytokine gene polymorphisms in the levels of these mediators and their impact on GVHD. This study aimed to investigate the impact of polymorphisms in the IL1B, IL6, IL10, IFNG and TNFA in levels of these cytokines in blood and saliva, and the relationship with the occurrence and severity of GVHD. We obtained blood samples and / or saliva of 58 patients and their donors for the analysis of polymorphisms in the IL1B, IL6, IL10, IFNG and TNFA using PCR. Bloodsamples and saliva were collected weekly seven days before transplantation (day -7) until day 100 post-transplant (day + 100) or even before the death of patients in order to assess the levels of cytokines by ELISA. The results showed no association between the occurrence of GVHD and polymorphisms evaluated. When we assessed the occurrence of disease in isolated organs, we observed relationship between donor TNFA genotypes and the greater severity of GVHD in the gut and skin. When the cytokine levels were determined, weobserved association between the presence of GVHD and high levels of IL-6, in blood and saliva, high IL-10 levels, in saliva, high IFN-g levels, in saliva, and low levels of IL-1â, in blood. Furthermore, high levels of IL-1â in saliva were associated with CC genotype of the IL1B gene. Increased levels of IL-6 and IL-10 in saliva were associated with high producer phenotype of the IL6 gene, in donors, and IL10, in recipients, respectively. Association was observed between high levels of the IFN-g and IL-10, in blood, and high producer of the IL10 and IFNG genes, in recipients, respectively. Moreover, levels of TNF-á in blood and saliva showed no association with the occurrence of GVHD or with the genotypes of patients or donors. Ours results shown the relevance of the genetic study of patients and donors for the understanding of GVHD, as well ascytokines levels could represent a valuable tool for the determination of the the evolution, prevention and treatment of the GVHD.